2010
DOI: 10.2355/isijinternational.50.1879
|View full text |Cite
|
Sign up to set email alerts
|

Motion and Morphology of Triple Junction in Peritectic Reaction Analyzed by Quantitative Phase-field Model

Abstract: Of particular importance in this study is the recent development of the model based on thin-interface limit. Motion and morphology of triple junction during peritectic reaction process is analyzed for a model alloy system based on a quantitative-phase-field simulation for two-phase solidification involving diffusion in the solid. It is demonstrated that the dominative process controlling the motion of the reaction front gradually changes from the solid-solid transformation to the secondary solid solidification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…These simulations are in excellent agreement with the experimental observations of the present study. Ohno et al 17) also investigated the influence of the partition coefficient on the morphology of the phases near the triple point, which is also in excellent agreement with our experimental observations.…”
Section: Peritectic Reactionsupporting
confidence: 89%
See 1 more Smart Citation
“…These simulations are in excellent agreement with the experimental observations of the present study. Ohno et al 17) also investigated the influence of the partition coefficient on the morphology of the phases near the triple point, which is also in excellent agreement with our experimental observations.…”
Section: Peritectic Reactionsupporting
confidence: 89%
“…A comparison between these different alloying systems leads to the conclusion that the peritectic reaction can actually be described as the solidification of γ along the L/δ interface, whereas the peritectic transformation is the diffusion-controlled growth of γ into the δ and the liquid phase, respectively. Ohno et al 17) investigated the morphology of the triple point for a model alloy system by means of quantitative-phase-field simulation, showing a strong effect of the solute diffusivity on the morphology of the triple point and the shape of the γ platelet.…”
Section: Peritectic Reactionmentioning
confidence: 99%
“…Phase-field simulations of primary ferrite dendrites that are later on covered by the peritectic austenite have been performed already at the end of the 1990's [82]. More recently, the effect of solid-state diffusion around the trijunction point and its influence on the spreading of the peritectic phase has been analyzed [83,84]. It was found that the presence of appreciable solidstate diffusion greatly reduces the melting of the primary phase and can drastically accelerate the spreading.…”
Section: Peritecticsmentioning
confidence: 99%
“…4a). The relation of the three phases is determined by the mechanical equilibrium condition [3,26]. Thus, a negative curvature of the a/L boundary (a groove structure) close to the triplephase point is required.…”
Section: Resolidification Of the Primary A Phasementioning
confidence: 99%